The future of design cognition analysis. (21st September 2020) - Hay, Laura; Cash, Philip; McKilligan, Seda
Abstract: 'Design cognition' refers to the mental processes and representations involved in designing, and has been a significant area of interest since the emergence of design research in the 1960s. The field now faces significant challenges moving into the future, with major change required to overcome stagnation in research topics and methodologies. Tackling these challenges requires us to understand the past and present of design cognition research, and open fresh discussions on its future. This thematic collection aims to address this need by taking stock of current approaches, exploring emerging topics and methodologies, and identifying future directions for enquiry. In this editorial, we examine key issues regarding both what we investigate and how we conduct this research. We present a vision formed from a structured literature review, the work of authors in the collection, and the views of a broad cross-section of the design cognition community. This vision is formalized in a roadmap from the present to the near and far future, highlighting key topics and research questions for the field. Ultimately, ecological measurement, new applications of artificial intelligence, and a move towards theory construction and research maturation constitute key long term challenges for the design cognition community.